PENGEMBANGAN LKPD BERBASIS INKUIRI PADA PENINGKATAN KEMAMPUAN PEMECAHAN MASALAH MATEMATIS - Fajar Solidman Larosa (LPPM Universitas Muhammadiyah Muara Bungo, 2023)
The lack of learning resources and mathematics teaching materials will affect the quality of students in mathematical problem-solving abilities. To overcome these obstacles, teaching materials are used that can improve the problem-solving ability of students. The purpose of this research is to develop valid, practical, and effective inquiry-based LKPD. This type of research is R&D (Research and Development) research. The development model used is the ADDIE model which consists of the stages of analysis, design, development, implementation, and evaluation. The subject of this study was a student of Nupela Private High School class X-IPA. The analysis stage is to analyze needs, curriculum, and students as a reference for development. The design phase results in the design of LKPD for mathematics learning. The development stage states that LKPD learning is feasible based on the validation of material experts by 93.33%, linguists by 91.11%, and media experts by 9.0%. The implementation phase stated that individual trials resulted in 87.08%, small group trials 8 8.75%, and field trials 99.25%, resulting in practical LKPD results of 9 1.69%. The evaluation stage states that the test results in the form of descriptions of 8.5% categories are very good so the inquiry LKPD meets the criteria of valid, practical, and effective.